Studi Pembuatan Procedure Qualification Record untuk Repair through Thickness pada S355 KT0 - Stefani, Windy; Leksonowati, Nur Fitria Pujo; Pamungkas, Nurman; Nugroho, Cahyo Budi (JURNAL INTEGRASI, 2024)
This research aims to develop a Procedure Qualification Record (PQR) for Repair Through Thickness on S355 KT0 material using the GTAW method for the root, SAW for filler and capping. The welds were repaired using gouging and grinding before undergoing repair welding with the SMAW method. The study employed experimental methods with Non-Destructive and Destructive tests following AWS D1.1 and Client Specification MHK-COMP-SPE standards. The test results indicate defect-free welds that meet AWS D1.1 standards in terms of mechanical properties such as tensile strength, bending, impact, and hardness. The tensile strength values reached 609 MPa (longitudinal specimen) and 539 MPa and 540 MPa for transverse specimens. The lowest impact test value was 139J in the fusion line +2 mm repair to original welds area. The peak hardness test value was 240 VHN in the HAZ (repair to original weld) region. The test results were also used to formulate a PQR that aligns with specific requirements. This research is expected to provide guidance for performing repair welding on S355 KT0 material.